2005
DOI: 10.1097/01.ico.0000151539.92865.3e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Topical Itraconazole 1% With Topical Natamycin 5% for the Treatment of Filamentous Fungal Keratitis

Abstract: Topical natamycin should continue to be considered as the treatment of choice for filamentous fungal keratitis; when natamycin is unavailable, topical itraconazole therapy could be used, particularly if the infections are due to Aspergillus or Curvularia spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 17 publications
2
61
0
3
Order By: Relevance
“…The study showed that in the Fusarium specific keratitis subgroup, response to natamycin was better than itraconazole (79 % of patients vs. 44 % of patients) (p=0.02). 39 Of note, a subgroup analysis of RCTs comparing the BSCVA (best spectacle-corrected visual acuity) and scar size between voriconazole and natamycin-treated patients showed no significant difference between the two agents. However, in voriconazole-treated Fusarium cases perforation of the cornea was more likely to occur than in Fusarium cases treated with natamycin.…”
Section: Natamycinmentioning
confidence: 99%
“…The study showed that in the Fusarium specific keratitis subgroup, response to natamycin was better than itraconazole (79 % of patients vs. 44 % of patients) (p=0.02). 39 Of note, a subgroup analysis of RCTs comparing the BSCVA (best spectacle-corrected visual acuity) and scar size between voriconazole and natamycin-treated patients showed no significant difference between the two agents. However, in voriconazole-treated Fusarium cases perforation of the cornea was more likely to occur than in Fusarium cases treated with natamycin.…”
Section: Natamycinmentioning
confidence: 99%
“…Natamycin (NAT), a tetraene polyene, has long been considered the mainstay of treatment for filamentous fungal keratitis and is the only available antifungal medication that has been approved for this indication by the U.S. Food and Drug Administration. Although previous reports regarding the efficacy of NAT in fungal keratitis are available (4-6), there are few studies that describe the in vitro activity of NAT against the common ocular isolates (2,7,8,9).The Clinical Laboratory and Standards Institute guidelines stress the use of pharmaceutical-grade powder solely for susceptibility testing. This is due to unknown purity and potency values and additives that may impact results (3).…”
mentioning
confidence: 99%
“…However, one cannot conclude from this study that the treatment modalities are equivalent. According to recently published data in the literature, topical natamycin continues to be considered the therapy of choice for treatment of filamentous keratitis (9) . Alfonso (19) reviewed cases of Fusarium keratitis at the Bascom Palmer Eye Institute, University of Miami, in a recent contact lens related outbreak of this disease in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Prajna et al (8) reported that a 2% preparation of econazole for topical application was as effective as 5% natamycin in the management of filamentous fungal keratitis. Kalavathy et al (9) compared topical 1% itraconazole with 5% natamycin and reported that natamycin should continue to be the treatment of choice for filamentous fungal keratitis. However, in many developing nations, natamycin and azole compounds are not readily available or affordable.…”
Section: Introductionmentioning
confidence: 99%